The Effect of Job Placement and Leadership Style on Employee Performance with Work Discipline as an Intervening Variable in the Pltmg Mpp Manokwari 2 Company - Tika Ayu Putri Iriyanti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of job placement and leadership style on employee performance with work discipline as an intervening variable at PLTMG MPP Manokwari 2. The research applies a quantitative approach using the Partial Least Square (PLS) analysis method. The population consists of all 36 employees of PLTMG MPP Manokwari 2, using a saturated sampling technique. The results show that job placement and leadership style have a positive and significant effect on employee performance. Both variables also have a positive and significant effect on work discipline. Furthermore, work discipline has a positive and significant effect on employee performance and acts as an intervening variable in the relationship between job placement and leadership style toward performance. Therefore, proper job placement, effective leadership, and high work discipline can optimally improve employee performance at PLTMG MPP Manokwari 2.